Dynamics of Implementing Digital Technology Development in Sociology Learning - Andrias Yovi Eka Listyawan; Ravik Karsidi; Argyo Demartoto (SEAMEO SEAMOLEC, 2025)
The development of technology in the era of the Fourth Industrial Revolution has brought significant changes in various aspects of human life, one of which is in the field of education. The integration of education is key in transforming the paradigm of education. With rapid changes, it demands a more innovative education system, not only in the use of technology but also in ensuring sustainability and access to education for everyone. However, challenges such as the digital divide, infrastructure readiness, and the lack of digital literacy among teachers and students remain major obstacles. This research aims to understand the role of training in enhancing the digital competence of Sociology teachers. The main theory used is Paulo Freire's liberating education. This research method uses descriptive qualitative with a case study method. Data were collected through observation, documentation, and questionnaires from the training participants. Then the data was analyzed using the Miles and Huberman model. The research results show that: (1) the training is able to enhance teachers' understanding of digital technology, (2) there is a transformation of learning into a student-oriented approach through problem-based learning, (3) teachers are starting to integrate artificial intelligence to prepare teaching materials and assessments.